IDEAL DIFERENSIAL DAN HOMOMORFISMA DIFERENSIAL - Na'imah Hijriati; Saman Abdurrahman; Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
Ideal differential is the ideal of differential ring that satisfies if for each a  I, and every   ,  (a)  I, whereas the differential homomorphism is a commutative homomorphism of rings against each derivation. This paper is presented the properties of differential ideal and differential homomorphism.